Development of Learning Videos Using Wondershare Filmora Software on Acid and Base Material at SMAN 1 Sungayang - Suci Putri Andani; Elvy Rahmi Mawarnis; Mimi Herman (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This research was carried out due to the lack of creativity of teachers in using learning media, students were bored following traditional learning, and the low results of student exams. Thus, it is necessary to develop a media in the form of learning videos using Wondershare Filmora software. The purpose of this research is to produce learning videos using Wondershare Filmora software on acid and base material that are valid and practical. This study uses the 4-D research method (define, design, develop, and disseminate). But in this study only carried out from the first stage to the third stage. Data for the defining stage was collected using an interview sheet. Data for the development stage was collected with validity sheets and practicality questionnaires. Validation was completed by 3 validators. Practicality questionnaire sheets were completed by the students in SMAN 1 Sungayang. Data from validity and practicality instruments were analyzed using descriptive quantitative methods, with the percentage formula. The results showed that: 1) learning videos using Wondershare Filmora software acid and base material at SMA N 1 Sungayang have met highly valid criteria with a validation result of 88.33%, 2) learning videos using Wondershare Filmora software on acid and base material at SMA N 1 Sungayang has fulfilled the highly practical criteria with a response questionnaire of 85.67%. The results of this study indicate that learning videos using the Wondershare Filmora software are valid and practical and can be used as a learning resource.